2021
DOI: 10.1007/s11423-021-10032-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing university teachers’ use of a mobile technology-enhanced teaching (MTT) platform

Abstract: The main purpose of this study was to examine the critical factors influencing university teachers’ use of a mobile technology-enhanced teaching (MTT) platform during the new coronavirus (COVID-19) epidemic. An integrated model with multiple factors drawing from the theoretical models and learning theories was proposed in this study to examine university teachers’ intentions to use an MTT platform. The multiple factors included the individual factor (e.g., growth mindset, help seeking, and self-efficacy), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 71 publications
4
30
2
1
Order By: Relevance
“…Future research is suggested to investigate students’ intentions and use of specific digital platforms and online environments, as well as Universities’ digital infrastructure. For example, mobile technology has a good potential for online education, and mobile technology-enhanced teaching platforms were adopted during the pandemic (Tang et al, 2021 ). Future research could also investigate opportunities that come with online education in the post-pandemic era.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Future research is suggested to investigate students’ intentions and use of specific digital platforms and online environments, as well as Universities’ digital infrastructure. For example, mobile technology has a good potential for online education, and mobile technology-enhanced teaching platforms were adopted during the pandemic (Tang et al, 2021 ). Future research could also investigate opportunities that come with online education in the post-pandemic era.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…PU is "the degree to which a person believes that using the new technology would enhance his or her job performance" (Davis, 1989). Following TPB, the perceived utility also influenced how users perceived adopting the new technology system amidst the coronavirus crisis (Tang et al, 2021;Mustafa et al, 2021;Han and Sa, 2022). The subsequent hypotheses are presented as:…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
“…To explain this scenario, it is possible that teachers were trained to integrate technology for educational purposes [30] and they had sufficient knowledge on how to adopt technology to deliver teaching [22], [27], resulting in their positive acceptance towards technology use for emergency remote teaching. The studies showed that teachers perceive technology has a facilitating effect in delivering the content knowledge to learners effectively during the pandemic [22], [23], [25], [27], [28], [34], [35], [37], [40], and they were comfortable and confident using online platforms to deliver lessons during the closure of educational institutions [22], [40]. This is supported by Zamora-Antuñano et al [45] which found that teachers managed to implement technology for emergency remote teaching because they received adequate training to confront the outbreak.…”
Section: Teachers' Technology Acceptance Level For Emergency Remote T...mentioning
confidence: 99%
“…There are five key factors that impact teachers' behavioral intentions to accept technology for emergency remote teaching during the COVID-19 pandemic, namely perceived usefulness or performance expectancy, perceived ease of use or effort expectancy, attitude toward use, social influence or subjective norm and facilitating conditions or perceived behavioral control. Among all the factors stated, PU [23], [24], [28], [33], [35], [37], [40], [43] or PE [27], [29], [41] is considered the most influential factor of teachers' intentions in accepting technology during the outbreak. In other words, teachers concern the most about how useful the technology is in enhancing their performance [54].…”
Section: Key Factors Affecting Teachers' Behavioral Intentions To Acc...mentioning
confidence: 99%